Exploration of factors predictive of at-risk fathers' participation in a pilot study of an augmented evidence-based parent training program: A mixed methods approach. (August 2017) - Rostad, Whitney L.; Self-Brown, Shannon; Boyd, Clinton; Osborne, Melissa; Patterson, Alexandria
Abstract: There has been burgeoning parenting intervention research specifically addressing fathers in recent decades. Corresponding research examining their participation and engagement in evidence-based parent training programs, which have almost exclusively targeted mothers, is just emerging. The current study used mixed methods to examine factors that influenced completion of an augmented version of an evidence-based child maltreatment prevention program developed for male caregivers called SafeCare Dad to Kids (Dad2K) in a pilot study. The current sample comprised 50 male caregivers ( M age  = 29.42 years, SD = 8.18) of a child between the ages of 2 and 5 years. Fathers participated in a baseline assessment and were considered program completers (n = 27) if they participated in the program's six home visiting sessions. A subsample of completers (n = 11) was recruited to participate in qualitative interviews that provided in-depth information about fathers' experiences in Dad2K. Logistic regression indicated that, in the context of other demographic predictors, fathers with an education beyond high school were over 5 times more likely to complete Dad2K program compared to fathers with a high school education or less. Qualitative analyses revealed that interviewed father completers were motivated to enroll and participate in a fathering program because of an interest to learn and obtain skills to make them a better parent. Fathers with a high school education or less may require additional engagement strategies to help proactively encourage their enrollment and completion of parent training programs. Highlights: Few home-based parent training programs have been developed specifically for fathers At-risk fathers with more than a high school education are more likely to complete a parenting program adapted for fathers Fathering programs should enhance initial motivation and develop strategies to engage fathers with lower education